if p x is equal to 4 x cube minus 3 X square + 2 x minus 4 then using the remainder theorem find the remainder when p x is divided by X + 1 and X - 1
Answers
Answered by
1
Answer:
0
Here p(x)=x
3
−2x
2
−4x−1 and g(x)=x+1
Now, p(x) is divided by g(x)
Thus the remainder is p(−1)=(−1)
3
−2(−1)
2
−4(−1)−1 (By Remainder Theorem)
=−1−2+4−1
=0
Thus, remainder is 0
Similar questions
Math,
1 month ago
Math,
1 month ago
History,
1 month ago
Math,
3 months ago
English,
11 months ago
Business Studies,
11 months ago
Social Sciences,
11 months ago